Implementasi Algoritma Apriori pada Pola Penjualan Produk Rumah Tangga Berbasis Web (Studi Kasus: Toko Subur Furniture) - Tema Putra Telaumbanua (CV. Multi Kreasi Media, 2026)
This study aims to implement the Apriori algorithm in a web-based system to analyze household product sales patterns at Toko Subur Furniture. The problem addressed is the absence of a system capable of identifying relationships among products based on sales transaction data, making it difficult to determine effective marketing strategies. The system was developed using the Waterfall methodology, which includes requirement analysis, system design, implementation, testing, and maintenance. The Apriori algorithm was applied to generate association rules based on minimum support and minimum confidence values. The results indicate that the developed system can identify customer purchasing patterns, helping store owners improve product arrangement, sales strategies, and promotional planning. In addition, the application simplifies sales data management and provides accurate reports efficiently.